Prediction of Scabertopin from Tapak Liman (Elephantopus scaber) for Antileukemic - Saristiana, Yuneka; Prasetyawan, Fendy; Salmasfattah, Novynanda; Ilmi, Tsamrotul; Fadel, Muhammad Nurul; Besan, Emma Jayanti (Marasofi International Media and Publishing (MIMP), 2025)
Leukemia remains a significant global health challenge, necessitating the exploration of novel therapeutic agents with improved efficacy and safety profiles. Elephantopus scaber (commonly known as Tapak Liman) is a medicinal plant traditionally used for various ailments, including cancer. Scabertopin, a sesquiterpene lactone isolated from E. scaber, has attracted scientific interest due to its potential antileukemic properties. This study aims to predict the antileukemic activity of Scabertopin through an in silico approach. The compound's chemical structure was retrieved in SMILES format from the PubChem database and analyzed using the PASS (Prediction of Activity Spectra for Substances) online tool. The prediction results indicated a high probability of antileukemic activity, with a Pa (probability of activity) value of 0.822 and a Pi (probability of inactivity) value of 0.004. These findings suggest a strong likelihood that Scabertopin exhibits antileukemic effects, supporting its potential as a candidate for further pharmacological and clinical investigations. The use of computational prediction tools provides an efficient and cost-effective preliminary screening method for identifying promising bioactive compounds from natural sources. This study contributes valuable insights into the therapeutic potential of Scabertopin and highlights the importance of traditional medicinal plants in drug discovery for leukemia treatment.